Glutathione alleviates the cadmium exposure-caused porcine oocyte meiotic defects via eliminating the excessive ROS. (December 2019) - Zhou, Changyin; Zhang, Xue; Chen, Yixuan; Liu, Xiangping; Sun, Yuxin; Xiong, Bo
Abstract: Heavy metal cadmium (Cd) is a widespread environmental contaminant with a potential toxicity that might adversely influence the health of experimental animals and humans. It has been known that Cd might accumulate in vertebrates for many years and thus leads to the hepatic and renal toxicity. Additionally, Cd concentration in the ovary increases with age and is highly related to the reproductive hazard. However, the underlying mechanisms regarding how Cd affects the female reproductive system especially the oocyte quality have not yet fully defined. Here, we reported that Cd exposure led to the defective nuclear maturation of oocytes via the impairment of cytoskeleton assembly, displaying the aberrant spindle organization, chromosome alignment and actin polymerization. In the meantime, Cd exposure caused the impaired cytoplasmic maturation by showing the disrupted dynamics of mitochondrial integrity and cortical granules, and thereby resulting in the compromised sperm binding ability and fertilization capacity of oocytes. More importantly, we found that glutathione (GSH) supplementation was able to recover the meiotic failure induced by Cd exposure through suppressing the excessive ROS level, DNA damage accumulation and apoptotic incidence. Taken together, our findings demonstrate that Cd exposure has the adverse effects on the oocyte meiotic maturation as well as subsequent fertilization, and provide a potential effective strategy to improve the quality of Cd-exposed oocytes. Graphical abstract: Image 1 Highlights: Cd exposure led to the defective nuclear maturation of oocytes via the impairment of cytoskeleton assembly. Cd exposure caused impaired cytoplasmic maturation of oocytes by disrupting dynamics of mitochondria and cortical granules. Cd exposure resulted in the compromised sperm binding ability and fertilization capacity of oocytes. Glutathione supplementation recovered the meiotic failure induced by Cd exposure through eliminating the excessive ROS.